Ultrasound dopplerography in evaluating the results of treatment of transversal anomalies with consumption mirofunctional equipment - Zakalata, T.; Chugu Т.; Isakova, N. (Actual Dentistry, 2018)
Summary. Morphological changes in the structure of supramaxilla result in the expressed changes in the coordinated work of masseters. Wide introduction in practice of orthodontia of modern types of orthodontic technique allow to get the functionally-proof and aesthetic results of treatment, however there is a question of efficiency of treatment in the age-related aspect. In spite of it, at orthodontic treatment case-insensitive the age-related aspect the undesirable side effects conditioned by the use of too large orthodontic forces and the use of unremovable orthodontic apparatus is unjustified widespread are marked. Key words: transversal anomalies, dentoalveolar anomalies, anthropometric indices.